1909 N.D. Laws 203 - (:unkn) unknown (My University, 1909)
Ch. 165, § 1: No body of men, other than the regularly organized corps of the national guard and militia and the troops of the United States, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state.
Keywords: MILITIAS